Sex Differences in Spatial Learning and Memory in Valproic Acid Rat Model of Autism: Possible Beneficial Role of Exercise Interventions - Ghahremani, Reza; Mohammadkhani, Reihaneh; Salehi, Iraj; Karimi, Seyed Asaad; Zarei, Mohammad (Frontiers in behavioral neuroscience, 2022)
In the current study, we first tried to determine sex differences in spatial learning and memory in the valproic acid (VPA) rat model of autism. Second, the effects of interval training (IT) and continuous training (CT) exercises were examined in male and female offsprings. To induce autism-like animal model, the pregnant rats were injected 500 mg/kg NaVPA (intraperitoneal) at the embryonic day 12.5. IT and CT aerobic exercises were started at postnatal day 56. Then, on postnatal days 84–89, a Morris water maze (MWM) test was conducted on the separate groups of offsprings. Aerobic training was performed on a rodent treadmill with 0% slope for 8 weeks, 5 days/week, and 50 min/day. Unlike control animals, VPA-exposed female offspring had a better performance than VPA-exposed male offspring in MWM acquisition. In the case of MWM reference memory, we did not observe a sex difference between VPA-exposed male and VPA-exposed female offspring. Both IT and CT exercises in both control and VPA-exposed male rats significantly improved MWM acquisition. Moreover, both IT and CT exercises significantly improved MWM acquisition in control female rats. In addition, IT exercise (but not CT) significantly improved MWM acquisition in VPA-exposed female offsprings. Both IT and CT exercises in VPA-exposed that male and female offsprings improved the MWM reference memory. In conclusion, our observation demonstrated that prenatal exposure to VPA affects the spatial learning and memory in a sex dependent manner. We have shown that both IT and CT exercises are able to improve cognitive function in healthy and autistic rat offsprings.